1983
DOI: 10.1063/1.525607
|View full text |Cite
|
Sign up to set email alerts
|

When is the Wigner function of multidimensional systems nonnegative?

Abstract: It is shown that, for systems with an arbitrary number of degrees of freedom, a necessary and sufficient condition for the Wigner function to be nonnegative is that the corresponding state wavefunction is the exponential of a quadratic form. This result generalizes the one obtained by Hudson [Rep. Math. Phys. 6, 249 (1974)] for one-dimensional systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
88
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 5 publications
2
88
0
Order By: Relevance
“…Hence, including a negative Wigner function element is mandatory in order to design a CV sub-universal quantum circuit that cannot be efficiently simulated by a classical device. By virtue of the Hudson theorem [10], this necessarily corresponds to the use of non-Gaussian resources.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, including a negative Wigner function element is mandatory in order to design a CV sub-universal quantum circuit that cannot be efficiently simulated by a classical device. By virtue of the Hudson theorem [10], this necessarily corresponds to the use of non-Gaussian resources.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed Hudson [4] showed that the only pure states ψ(x) for which the Wigner function is non-negative are Gaussian in x. This carries over to any number of dimensions [6], and also, for odd dimensions at least, to the formulation of discrete Wigner functions [7].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, if any Wigner function is convoluted, or smeared, by integration with respect to the Wigner function of the vacuum state, itself a gaussian function on phase space, then the smoothed function, called the Q-function (or Husimi function), is non-negative and corresponds to an ordering in Cohen's class different from that of Wigner and Weyl [9]. More generally, if any Wigner function is convoluted with respect to a Gaussian function which is itself the Wigner function of a pure coherent state, then the result is non-negative [6,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…All WDFs of higher-order functions have regions with negative values. 7 Due to these negative values the WDF is able to account for interference effects. Table 1: The WDF of some commonly used electric fields.The propagation distance along the optical axis is represented by z, the wavenumber by k and the two-dimensional spatial frequencies by the vector k.…”
mentioning
confidence: 99%